Managing Large-Scale Capital Inflows : The Case of the Czech Republic, Poland and Romania - Keller, Leonor (IMF Working Papers; Working Paper ;, 2012)
Many emerging market economies have in the recent past experienced a surge in capital inflows that may threaten their economic and financial stability. The IMF in early 2011 proposed a framework intended to guide Fund advice to policymakers on how to best respond to such inflows, including both macroeconomic instruments and so-called capital flow management measures (CFMs). The paper applies this framework to three countries that have experienced elevated capital inflows after the onset of the 2008 global financial crisis - the Czech Republic, Poland, and Romania. It finds that the evaluation of the macroeconomic criteria as prescribed by the framework does not support the use of CFMs, but instead advocates macroeconomic policies as the first line of defense against large-scale capital inflows. This finding is by and large consistent with the IMF's policy advice given to country authorities in the context of surveillance missions.